2021
DOI: 10.1038/s41419-020-03382-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles-released parathyroid hormone-related protein from Lewis lung carcinoma induces lipolysis and adipose tissue browning in cancer cachexia

Abstract: Cancer cachexia is a metabolic disorder characterized by skeletal muscle wasting and white adipose tissue browning. Specific functions of several hormones, growth factors, and cytokines derived from tumors can trigger cachexia. Moreover, adipose tissue lipolysis might explain weight loss that occurs owing to cachexia. Extracellular vesicles (EVs) are involved in intercellular communication. However, whether EVs participate in lipolysis induced by cancer cachexia has not been thoroughly investigated. Using Lewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Circulating PTHrP, a paraneoplastic factor that induces hypercalcaemia, has been shown to indirectly increase HSL phosphorylation, which is required for HSL enzymatic lipase activity, through protein kinase A. 18 , 36 , 37 PTHrP is also reportedly associated with browning via increased UCP‐1 protein 17 in AT in rodent models, making its impact on thermogenesis and lipolysis difficult to differentiate. Other groups have reported that cancer patients with detectable circulating PTHrP levels have higher relative REE 17 and reduced body fat 19 than those with undetectable PTHrP.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating PTHrP, a paraneoplastic factor that induces hypercalcaemia, has been shown to indirectly increase HSL phosphorylation, which is required for HSL enzymatic lipase activity, through protein kinase A. 18 , 36 , 37 PTHrP is also reportedly associated with browning via increased UCP‐1 protein 17 in AT in rodent models, making its impact on thermogenesis and lipolysis difficult to differentiate. Other groups have reported that cancer patients with detectable circulating PTHrP levels have higher relative REE 17 and reduced body fat 19 than those with undetectable PTHrP.…”
Section: Discussionmentioning
confidence: 99%
“…99 Interestingly, it was shown that LLC tumors are able to release extracellular vesicles (EVs) containing PTHrP, and this event induces lipolysis in 3T3-L1 adipocytes in vitro. 100 In in vivo conditions, the same EVs-containing PTHrP were found to be important drivers of fat loss and WAT browning in LLC bearers. 100 Altogether, these observations support PTHrP as a new target to counteract muscle, WAT, and bone loss during cancer cachexia.…”
Section: Osteokines In Muscle-bone Crosstalkmentioning
confidence: 96%
“…100 In in vivo conditions, the same EVs-containing PTHrP were found to be important drivers of fat loss and WAT browning in LLC bearers. 100 Altogether, these observations support PTHrP as a new target to counteract muscle, WAT, and bone loss during cancer cachexia.…”
Section: Osteokines In Muscle-bone Crosstalkmentioning
confidence: 96%
“…8486 Table 2 summarizes the mechanism of cachexia. 13,14,34,87124 The broad picture of CC is summarized in Figure 1.…”
Section: Imbalance Of Anabolism and Catabolism: Insight Into The Mole...mentioning
confidence: 99%
“…151154 Mechanistic studies conducted by Zhang et al 155 showed that EV-derived HSP70 and HSP90 activate Toll-like receptor 4 (TLR4) and p38–MAPK pathways resulting in CC, and that this is prevented by either neutralizing or silencing HSP70 and HSP90 in LLC cells. Recently, Hu et al 106 demonstrated that LLC cell-derived EVs induce lipolysis both in vitro and in vivo by delivering the parathyroid hormone–related protein (PTHrP) which interacts with its receptor parathyroid hormone receptor (PTHR) to exert downstream effects. Similar observations were made by Yang et al 156 in 2019 in pancreatic tumor xenograft models.…”
Section: Imbalance Of Anabolism and Catabolism: Insight Into The Mole...mentioning
confidence: 99%